REPLACEMENT OF THE WHOLE DESCENDING THORACIC AORTIC ANEURYSM WITH A TUBULAR GRAFT BY INCORPORATING CENTRIFUGAL PUMP AND INTRA-OPERATIVE CELL SALVAGE MACHINE: Descending Thoracic Arotic Aneurysm - Nafees, Syed Shahid; Waseem, Muhammad; Rashid, Azhar; Khan, Asif Ali; Rao, Tariq (Pakistan Armed Forces Medical Journal, 2009)
INTRODUCTIONThoracic aortic aneurysm is a serious health entity which when gets ruptured leads to death of fifty percent of the patients before reaching the hospital. Out of those 50% which reach hospital, approximately 75% percent die later in the hospital.Incidence of these aneurysms is 6 cases per hundred thousand populations per year. Overall prevalence of aneurysm is increasing in the last thirty years, which is in part due to wide spread use of the imaging techniques [1].Elective repair of these aneurysms is done either by open surgical method or by employing endovascular stents. In open surgical repair, there is moderate to severe bleeding which demands repeated blood transfusions which in turn have its own attendant risks and side-effects. This problem of heavy blood loss is solved, in great part, by employing a relatively new gadget called Intra-operative salvage machine (also called cell-saver). This cell-saver collects the shed blood, washes, concentrates and finally stores it for re-infusion to the patient. Here we case report a surgically treated case of thoracic aortic aneurysm using centrifugal pump and cell-saver at AFIC/NIHD Rawalpindi.